UWRF CAFES internship program evaluation-2011 - Hadley, Shelly; Riedeman, Caleb; Trechter, David (My University, 2011)
The motivation for this annual study was to evaluate intern experiences of the College of Agriculture, Food and Environmental Sciences (CAFES) students at the University of Wisconsin-River Falls (UWRF).
43 p.
Keywords: College students; Students; College of Agriculture, Food and Environmental Sciences; University of Wisconsin-River Falls. College of Agriculture, Food and Environmental Sciences; University of Wisconsin-River Falls--Students; Internship program; Internships; College students--Wisconsin--River Falls